Anti-inflammatory Effect of Pequi Oil (Caryocar brasiliense) in Acute Respiratory Distress Syndrome - Sousa,, Tawanne Costa de (Journal of Medical Biomedical and Applied Sciences, 2014)
Introduction: Acute lung lesion (ALL) and the more severe form, acute respiratory distress syndrome (ARDS), are the common denominator of many diseases that can cause exaggerated lung inflammationÂ Objectives:Â The aim of this study was to analyze the anti-inflammatory action of pequi oil (Caryocar brasiliense) in an experimental model of acute lung inflammation induced in mice.Â Methods:Â Fifteen maleÂ RattusÂ novergicusÂ were divided into three groups: falsely operated (abdominal incision), sham (ischemia and intestinal reperfusion â I/R-1 without treatment); treated (I/R + pequi essential oil).Â  Results: The treated group had less inflammatory cells, when compared with the sham group (p<0.001). Moreover, the results suggest that the treated group did not significantly differ from the falsely operated group.Â Conclusion:Â It is suggested that nebulized pequi oil reduces the pulmonary inflammatory response to injury resulting from the I/R-i lesion.